2020
DOI: 10.1038/s41598-020-70158-z
|View full text |Cite
|
Sign up to set email alerts
|

Fully biological production of adipic acid analogs from branched catechols

Abstract: Microbial production of adipic acid from lignin-derived monomers, such as catechol, is a greener alternative to the petrochemical-based process. Here, we produced adipic acid from catechol using catechol 1,2-dioxygenase (CatA) and a muconic acid reductase (MAR) in Escherichia coli. As the reaction progressed, the pH of the media dropped from 7 to 4-5 and the muconic acid isomerized from the cis,cis (ccMA) to the cis,trans (ctMA) isomer. Feeding experiments suggested that cells preferentially uptook ctMA and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Mono- and polycarboxylic acids (mono- and poly-CAs) are ubiquitous in nature and represent a large repository of platform chemical precursors . Several reports have shown that CAs can be derived from biomass-based resources such as lignin and hemicellulose using green and economically feasible methods. , Likewise, many different methods for producing dicarboxylic acids (di-CAs) from biomass have been developed. Although the produced CAs are valuable by themselves, their corresponding terminal alcohols (ALs) are more interesting as platform chemicals, as they may find useful applications in the production of polymers and as fuel additives to improve the octane number. Moreover, terminal ALs are in general synthetically more useful than the parent CAs.…”
Section: Introductionmentioning
confidence: 99%
“…Mono- and polycarboxylic acids (mono- and poly-CAs) are ubiquitous in nature and represent a large repository of platform chemical precursors . Several reports have shown that CAs can be derived from biomass-based resources such as lignin and hemicellulose using green and economically feasible methods. , Likewise, many different methods for producing dicarboxylic acids (di-CAs) from biomass have been developed. Although the produced CAs are valuable by themselves, their corresponding terminal alcohols (ALs) are more interesting as platform chemicals, as they may find useful applications in the production of polymers and as fuel additives to improve the octane number. Moreover, terminal ALs are in general synthetically more useful than the parent CAs.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements to this synthetic pathway performed afterwards increased the titers to ~2 mg/L (see details in Supplementary Table S1 and in Table 2). Among the modifications performed in E. coli, the use of an enoate reductase from Clostridium acetobutylicum was the most successful [57]. S1.…”
Section: Adipic Acidmentioning
confidence: 99%
“…These precursors were then further catalyzed into adipic acid in a hydrogenation process using the precious metal Pt as a catalyst. ,, However, the use of Pt greatly increases production costs. Recently, muconic acid reductase (MAR) has been proven to reduce cis , cis -muconic acid to adipic acid and has been applied for the full biological production of adipic acid. , However, the low titer and high price of cis , cis -muconic acid still hinder the large-scale industrial production of adipic acid. In addition, various biosynthetic routes that are independent of the chemical synthesis processes have been established in recent years, such as the reversal of the β-oxidation pathway , and the ω-oxidation of the fatty acids pathway , and the α-keto acid pathway. , However, these approaches are limited by the low adipic acid titer and the expensive precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, muconic acid reductase (MAR) has been proven to reduce cis,cis-muconic acid to adipic acid and has been applied for the full biological production of adipic acid. 13,14 However, the low titer and high price of cis,cis-muconic acid still hinder the large-scale industrial production of adipic acid. In addition, various biosynthetic routes that are independent of the chemical synthesis processes have been established in recent years, such as the reversal of the β-oxidation pathway 15,16 and the ω-oxidation of the fatty acids pathway 1,17 and the α-keto acid pathway.…”
Section: ■ Introductionmentioning
confidence: 99%